2008
DOI: 10.1002/nag.742
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution to 1D coupled water infiltration and deformation in unsaturated soils

Abstract: SUMMARYAn analytical solution to 1D coupled water infiltration and deformation is derived using a Fourier integral transform. Exponential functional forms are used to represent the hydraulic conductivity-pore-water pressure relationship and the soil-water characteristic curve. Fredlund's incremental-linear constitutive model for unsaturated soils is adopted. The analytical solution considers arbitrary initial pore-water pressure distributions and flux and pressure boundary conditions. The corresponding analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…For instance, [6][7][8] used analytical solutions to study the effect of hydraulic parameters and rainfall conditions on the infiltration of unsaturated homogeneous and two-layered soils. These studies showed the influence of the hydrology and hydraulic parameters of the materials on changes on the pore water pressures and volumetric strains.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [6][7][8] used analytical solutions to study the effect of hydraulic parameters and rainfall conditions on the infiltration of unsaturated homogeneous and two-layered soils. These studies showed the influence of the hydrology and hydraulic parameters of the materials on changes on the pore water pressures and volumetric strains.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Darcy's Law and conservation of the 1D fluid mass, combined with the stress-strain relationship applicable to normal strains proposed by Fredlund and Rahardjo [24], the 1D governing equation for partially saturated infiltration coupled with deformation in a semi-infinite domain, where the water compressibility is neglected, can be given as [11,14] …”
Section: Analytical Solution To the Coupled Infiltration In A Semi-inmentioning
confidence: 99%
“…Srivastava and Yeh [5] derived an analytical approach to describe one-dimensional rainfall infiltration towards the water table. In recent years, analytical solutions to the one-dimensional problem incorporating rainfall-induced hydromechanical coupling in unsaturated porous media have been developed [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Zhang (2009) presented an analytical solution to one-dimensional coupled water infiltration and deformation, which is derived by adopting the exponential functional forms for soil-water characteristic curve and permeability function.…”
Section: Coupled Hydro-mechanical Analysismentioning
confidence: 99%